Assessment of Water Quality Parameters in Penaeus monodon Culture Ponds: Implications for Sustainable Shrimp Aquaculture - Tulus, Muh Yusril AL; Maulianawati, Diana (Aquatic Life Sciences, 2025)
Shrimp aquaculture depends on stable water quality, but fluctuations often reduce growth and survival, making optimal conditions essential for sustainable Penaeus monodon culture. This study aimed to evaluate key water quality parameters in two shrimp ponds and assess their suitability against established aquaculture standards. Field measurements and laboratory analyses were conducted over ten weeks across three sampling stations in each pond. Parameters measured included pH, temperature, salinity, dissolved oxygen (DO), nitrate, nitrite, ammonia, phosphate, and water hardness. Results showed that pH ranged from 7.29–7.80, temperature from 31.40–32.00 °C, salinity from 17.30–17.88 ppt, and DO from 5.29–5.87 mg/L, all within acceptable limits (SNI 8038.1:2014). Nutrient concentrations varied, with nitrate (0–0.4 mg/L), nitrite (0–0.4 mg/L), ammonia (0.1–0.4 mg/L), and phosphate (0–0.5 mg/L), where ammonia occasionally exceeded the safe threshold of 0.1 mg/L. Water hardness ranged from 0.17–0.43 mg/L CaCO₃, below the reference limit of 100 mg/L CaCO₃. Overall, the ponds provided suitable conditions for shrimp growth, but elevated nutrient levels at certain periods indicate the need for improved feed and waste management. Maintaining balanced water quality is essential to optimizing shrimp health, enhancing productivity, and ensuring the sustainability of aquaculture practices.